The Impact Of EECP On Improving Exercise Capacity In Patients With Stable Ischemic Heart Disease Who Treated Medically Or Percutaneously Over One Year - Jabbar Majeed, Ammar; Abdulruda Yasseen, Yasseen; Abdullah Alsallami, Ali Yahya; Ibrahim Amber, Khalid (Journal of Neonatal Surgery, 2025)
Objective: Enhanced External Counterpulsation (EECP) is a non-invasive therapy involving sequential inflation of external cuffs placed on the lower limbs in sync with the cardiac cycle. This method is primarily used to treat refractory angina (persistent for at least three months) in patients who do not respond to medical therapy, surgical intervention, or percutaneous coronary procedures. Methods: A total of 91 patients with refractory angina who were either unresponsive to medical therapy, ineligible for surgical intervention, or had undergone PCI without symptom relief were enrolled in the study. Patients were selected from the Al-Najaf Cardiac Center and private clinics between January 2018 and December 2019. All participants underwent coronary angiography, and those with significant three-vessel disease (>70% stenosis in each vessel) were included. Results: Over 12 months, 91 patients (32 women and 59 men) aged 45 to 80 years (mean 61 ± 8.2) were analyzed. Most patients completed an average of 26 EECP sessions (SD ± 7), with a response rate of 88.7%, as measured by symptom improvement based on Canadian Cardiovascular Society (CCS) classification. No significant difference in response to EECP was observed between the PCI group and those treated with medical therapy alone (p = 0.87, p = 0.47). Additionally, sex (p = 0.185), smoking history (p = 0.67), hypertension (p = 0.4), diabetes (p = 0.12), and age (p = 0.26) did not significantly impact the response to EECP. Conclusion: EECP proved to be a safe and effective treatment for select patients with refractory angina who were unresponsive to conventional medical or surgical interventions.